Sistem Informasi Manajemen Supervisi Akademik Berbasis Website dalam Peningkatan Kinerja Pengawas Sekolah - Herry Sanoto; Mila Chrismawati Paseleng; Dani Kusuma (AITI, 2022)
Academic supervision is one of the processes in an effort to improve the quality and professionalism of teachers through a process of regular supervision and coaching. Bengkayang Regency is one of the regencies in Indonesia that is included in the 3T criteria (Front, Outermost, Disadvantaged) with low academic supervision results, due to limited access and geographical conditions. The purpose of this study was to describe the impact of academic supervision carried out with a Management Information System (MIS) for academic supervision on the effectiveness of the performance of school supervisors. The research method used in this research is a mix method research method with a sequential exploratory model, which is a combination of qualitative and quantitative research. Qualitative analysis was carried out first to find out detailed data related to the supervision process carried out by school supervisors, while quantitative analysis was carried out by analyzing the differences in the achievements of academic supervision from before and after using the online supervision system. The research subjects used in the study were school supervisors in the Bengkayang district which consisted of 8 school supervisors. The research instruments used were questionnaires, interview guidelines, and documentation. The results showed that the Academic Supervision Management Information System (MIS) made it easier for school supervisors to carry out the academic supervises process. Through the system, the results of supervision have increased compared to the previous period. Tacademic supervisionhe online-based academic supervision system in general, is a solution to access limitations including distance, time, and the ratio of supervisors to supervised teachers. The suggestion in this study is that the use of an online-based academic supervision system can be used not only in the 3T area but can be applied in other areas, especially in the era of the covid-19 pandemic.